2001
DOI: 10.1038/sj.ejhg.5200715
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a nonsense mutation in the PAX9 gene in molar oligodontia

Abstract: Development of dentition is controlled by numerous genes, as has been shown by experimental animal studies and mutations that have been identified by genetic studies in man. Here we report a nonsense mutation in the PAX9 gene that is associated with molar tooth agenesis in a Finnish family. The A340T transversion creates a stop codon at lysine 114, and truncates the coded PAX9 protein at the end of the DNAbinding paired-box. All the affected members of the family were heterozygous for the mutation. The tooth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
133
0
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(146 citation statements)
references
References 15 publications
6
133
0
7
Order By: Relevance
“…Characteristically, when a premolar or molar tooth is missing, all the posterior teeth on the same hemiarch are also absent. 6,8,9,11 Oligodontia of molar teeth was most pronounced in a family with complete deletion of one copy of the PAX9 gene. 11 Our clinical analysis revealed that the pattern of tooth agenesis in the family we describe deviates from PAX9 phenotypes previously reported (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristically, when a premolar or molar tooth is missing, all the posterior teeth on the same hemiarch are also absent. 6,8,9,11 Oligodontia of molar teeth was most pronounced in a family with complete deletion of one copy of the PAX9 gene. 11 Our clinical analysis revealed that the pattern of tooth agenesis in the family we describe deviates from PAX9 phenotypes previously reported (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we favor the explanation that the third molars failed to form because they are the last teeth to develop from the dental placode and that the adverse effects of follistatin overexpression earlier in development had resulted in a deficiency of tissue committed to the molar field. This mechanism has been proposed previously as an explanation to the common observation that the most frequently missing teeth in humans are those that develop last in each tooth family (incisors, premolars, and molars; Miles and Grigson, 1990;Nieminen et al, 2001). It is not possible to pinpoint the actual function of the overexpressed follistatin, which led to third molar agenesis, because all epithelial and most mesenchymal cells were probably exposed to the follistatin protein during the entire time of tooth morphogenesis.…”
Section: Overexpression Of Follistatin Inhibits the Formation Of The mentioning
confidence: 96%
“…12,14 In humans, dominant mutations in PAX9 have been identified as a cause of congenital absence of some posterior (and occasionally anterior) teeth. Frame-shift, [15][16][17] insertion, 18,19 missense 18 and non-sense 20,21 mutations, as well as whole-gene deletion, 18,22,23 have been described in families exhibiting hypodontia, primarily with absence of molar teeth. In addition, it has been shown that common polymorphisms in PAX9 are associated with 3rd molar (M3) agenesis.…”
Section: Introductionmentioning
confidence: 99%